(untitled) (Research, Society and Development, 2020)
The present research aims to evaluate in silico the pharmacokinetics, pharmacodynamics and toxicological parameters of phytol and thymol isolated from Moringa oleífera. The pharmacokinetic and toxicological analysis was performed by the online server PreADMET which is maintained by the University of Seoul in South Korea and is available at (https://preadmet.bmdrc.kr/). The molecule’s source code (.mol) was inserted into the PreADMET server and the prediction in silico of several pharmacokinetic and toxicological parameters of phytol and thymol based on the structure-activity relationship of these molecules with other molecules previously researched and with its results available in various databases. In the pharmacodynamic analysis, another online server was used, the Swiss Target Prediction, where the targets that the molecules bound and the probability of binding were observed. According to PreADMET, the pharmacokinetic parameters analyzed, showed quite significant results with important molecular targets such as COX, GABA receptors and serotonergics for example, however, for toxicological parameters, they were reasonable, in which phytol proved to be favorable for carcinogenicity in rats, but not in mice, due to differences in physiology regarding metabolism and thymol was positive in the Ames Test in three strains, being negative in only one. It was possible to observe that a more in-depth study is needed to confirm the different types of molecular changes in order to improve the parameters that were not satisfactory.